Attack of the heroes : starring Spider-Man - Thomas, Rich (Mighty Marvel chapter book., 2017)
When the superheroes in the city start causing trouble instead of preventing it, it's up to Pater Parker as Spiderman to make them stop. And when Flash Thompson finds himself in the mix, Peter will have to put aside their differences to save the boy whose been bullying him at school.